HAEMATOLOGICAL AND HISTOPATHOLOGICAL ALTERATIONS DUE TO COMBINED TOXICITY OF ISONIAZID AND RIFAMPICIN; AMELIORATION WITH WITHANIA SOMNIFERA AND VITAMIN-E IN WISTAR RATS - S.ARUNDHATHI,; A.ANAND KUMAR,; Y.RAVI KUMAR,; B.ANIL KUMAR, (International Journal of Pharma and Bio Sciences, 2015)
The present study was designed to investigate the combined toxicity Isoniazid (ISN) and Rifampicin (RIF), which are widely used in treating tuberculosis; and protective effects of Withania somnifera and Vitamin E against the toxixcity induced ced by the drugs on haematological and histopathological alterations. The experimental study was conducted with healthy male Wistar rats (age 60-100 days, weighing 175-260mg) procured from National Institute of Nutrition, Hyderabad and the experiment was carried out according to the guidelines and prior approval of Institutional Animal Ethics Committee. Animals were divided into four groups consisting of 6 in each group. The experimental study was designed as follows:- Group 1-Control, Group II-ISN@50mg/kg body wt + RIF@100mg/kg body wt once daily orally for 21 days, Group III-ISN@50mg/kg body wt + RIF@100mg/kg body wt once daily orally for 21 days + Withania somnifera@1000mg/kg feed daily for 21 days, Group IV-ISN@50mg/kg body wt + RIF@100mg/kg body wt once daily orally for 21 days + vitamin E@300mg/kg feed daily for 21 days. The experiment was carried out for 21days and blood was collected 4 times at weekly intervals (0,7,14 and 21 days) for estimation of various haematological parameters and tissues were collected for histopathological studies. The hematological assays showed a significant reduction in packed cell volume, haemoglobin, total erythrocytes count and significant increase in total leucocytes count in group II in comparison to other groups. Histopathological changes were noticed significantly. In group II, liver showed severe sinusoidal congestion and mild congestion of central vein, portal tracks were enlarged and infiltrated with mononuclear cells, disorganization of hepatic cords and moderate to severe necrosis. Cardiac muscle fiber showed varied degree of injury, disruption and seperation of muscle bundles. In kidney, glomeruli revealed degeneration of tubules and haemorrhages in interstitial tubular spaces, disrupted tubules. Brain showed congestion and mononuclear cell infiltration surrounded by areas of fatty changes. The groups III and IV animals showed significant improvement in all parameters and tissue changes in comparison to group II by the ameliorative effects of Withania somnifera and vitamin E .